Research of Indonesian GHG Emission Assessment from Forest and Land Fires - Bambang Hero Saharjo (Jurnal Silvikultur Tropika, 2022)
Previous research has confirmed that efforts to control forest and land fires in Indonesia are not optimal so that fires still occur at a high escalation rate. This happens because very few research results are used to solve the problem of forest and land fires, so that useful information becomes useless. Research activities continue, which do not cover only technical issues of controlling forest and land fires but also the negative implications as a result, namely the production of GHG emissions, especially on peat land because it is one of the main sources of significant GHG emissions. What is also not important is the procedure for calculating GHG emissions, which based on this research actually results in overestimation of emissions from what should be produced. Of course, this needs to be straightened out so that Indonesia is not harmed just because it follows an inappropriate calculation. Keywords: Greenhouse gases, forest and land fires, research, peat, fire control